PENGARUH METODE HAPPY LEARNING TERHADAP ASPEK AFEKTIF PESERTA DIDIK DI MAN 1 KOTA TANGERANG - Pinkan Meitama, Ratu; Al Fahmi, Faiz Fikri; Rahmatullah, Muhammad Asep (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The Happy Learning method has emerged as an instructional approach to foster and develop students' moral character through the affective domain. Students may experience learning difficulties and demonstrate inappropriate attitudes when the learning environment is not designed to meet their needs. By implementing the Happy Learning method, the learning atmosphere becomes more enjoyable, enabling students to acquire knowledge more effectively. This study aimed to examine the effect of the Happy Learning method on students' affective domain and to determine the extent of its contribution. This research employed a quantitative method with a case study approach using simple linear regression analysis. Data were collected through questionnaires and documentation, and subsequently analyzed using the Statistical Package for the Social Sciences (SPSS) version 27. The sampling technique applied was proportional random sampling. The population consisted of 272 students, from which 162 students were selected as the research sample. The findings indicate that: (1) the Happy Learning method has a significant effect on the affective domain of students at MAN 1 Kota Tangerang, as evidenced by a t-value of 10.665 with a significance level of 0.001 (p < 0.05); and (2) the Happy Learning method contributes 41.6% to the students' affective domain, while the remaining 58.4% is influenced by other factors beyond the scope of this study.